2001
DOI: 10.1054/bjoc.2001.2187
|View full text |Cite
|
Sign up to set email alerts
|

Papillary thyroid carcinoma: 6 cases from 2 families with associated lymphocytic thyroiditis harbouring RET/PTC rearrangements

Abstract: Summary Familial papillary thyroid carcinoma (PTC) is a well recognized disease. However, genetic predisposition to familial PTC is rare and the molecular alterations at the origin of the pathology are unknown. The association between PTC and lymphocytic thyroiditis (LT) has been reported recently. We communicate here 6 cases of PTC associated with LT in 2 unrelated families. PTC was diagnosed on classical nuclear and architectural criteria. It was bilateral in 5 cases. Architecture was equally distributed bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…Indeed, RET/PTC expression was more likely to be found in occult or microcarcinomas of the thyroid than in poorly differentiated thyroid carcinomas, suggesting that RET/PTC activation is an early event in thyroid transformation (Viglietto et al, 1995;Bongarzone et al, 1996;Sugg et al, 1998;Fusco et al, 2002). Interestingly, RET/PTC expression has been frequently observed in patients afflicted with papillary thyroid carcinomas associated with autoimmune thyroiditis (Wirtschafter et al, 1997;Di Pasquale et al, 2001;Mechler et al, 2001) and in those patients with autoimmune thyroiditis but no pathologically detectable carcinoma (Wirtschafter et al, 1997;Sheils et al, 2000). Furthermore, patients diagnosed with autoimmune thyroiditis stained for c-RET protein, indicating that these specimens may express either an oncogenic RET/PTC family member or the protooncogene, c-RET, in thyroid epithelial cells (Di Pasquale et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, RET/PTC expression was more likely to be found in occult or microcarcinomas of the thyroid than in poorly differentiated thyroid carcinomas, suggesting that RET/PTC activation is an early event in thyroid transformation (Viglietto et al, 1995;Bongarzone et al, 1996;Sugg et al, 1998;Fusco et al, 2002). Interestingly, RET/PTC expression has been frequently observed in patients afflicted with papillary thyroid carcinomas associated with autoimmune thyroiditis (Wirtschafter et al, 1997;Di Pasquale et al, 2001;Mechler et al, 2001) and in those patients with autoimmune thyroiditis but no pathologically detectable carcinoma (Wirtschafter et al, 1997;Sheils et al, 2000). Furthermore, patients diagnosed with autoimmune thyroiditis stained for c-RET protein, indicating that these specimens may express either an oncogenic RET/PTC family member or the protooncogene, c-RET, in thyroid epithelial cells (Di Pasquale et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…RET/ PTC oncogenes are a family of fusion proteins derived from chromosomal rearrangements involving the tyrosine kinase domain of the c-RET proto-oncogene and are frequent mutations found early in the development of a variety of differentiated thyroid carcinomas (Jhiang et al, 1992;Santoro et al, 1992;Fusco et al, 1995;Takahashi et al, 1995;Fugazzola et al, 1996;Sugg et al, 1996;Bongarzone et al, 1997). Whereas RET/PTC expression has been frequently observed in patients affected with PTCs showing concurrent thyroiditis, its expression was also reported in thyroid tissue of patients afflicted with HT with no detectable cancer suggesting a common etiology of these two diseases (Wirtschafter et al, 1997;Sheils et al, 2000;Mechler et al, 2001;Pasquale et al, 2001). The association of RET/PTC with HT suggested that oncoproteins may be one component involved in promoting organ-specific inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The possible association between Hashimoto's thyroiditis (HT) and papillary thyroid carcinoma (PTC) remains controversial. The association between HT and PTC is also supported by the observation that rearrangements of the rearranged during transfection (RET) oncogene is frequently detected in PTC (9).…”
Section: Introductionmentioning
confidence: 84%